Civil engineering insurance and bonding - Edwards, Leslie (Thomas Telford, 1996)
Useful for engineers, this guide explains some of the basic principles and practices of civil engineering insurance. It concentrates on four main areas, namely the insurance of contract works during construction, public liability, employer's liability, and professional indemnity insurance.
Previous ed.: published as by Peter Madge. 1987.
Keywords: Business insurance -- Great Britain.; Construction industry -- Great Britain.; elektronické knihy; electronic books